2022
DOI: 10.1016/j.cyto.2022.155804
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profiles in the detection of severe lung involvement in hospitalized patients with COVID-19: The IL-8/IL-32 axis

Abstract: Coronavirus disease 2019 (COVID-19) is an infectious respiratory disorder caused by a new coronavirus called SARS-CoV-2. The pathophysiology of severe COVID-19 is associated with a “cytokine storm”. IL-32 is a key modulator in the pathogenesis of various clinical conditions and is mostly induced by IL-8. IL-32 modulates important inflammatory pathways (including TNF-α, IL-6 and IL-1b), contributing to the pathogenesis of inflammatory diseases. Il-32 was never evaluated before in COVID-19 patients stratifying a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 38 publications
4
23
1
Order By: Relevance
“…Significant differences at p < 0.05 are indicated by asterisk (*) as compared to NI and by connecting lines for comparisons between Discharge versus Death. (25) or increased levels in COVID-19 patients (30). Our findings indicated elevated levels of IL-1b only systemically in COVID-19 patients and no significance was found either in airway or when groups with distinct outcomes were compared.…”
Section: Discussioncontrasting
confidence: 65%
“…Significant differences at p < 0.05 are indicated by asterisk (*) as compared to NI and by connecting lines for comparisons between Discharge versus Death. (25) or increased levels in COVID-19 patients (30). Our findings indicated elevated levels of IL-1b only systemically in COVID-19 patients and no significance was found either in airway or when groups with distinct outcomes were compared.…”
Section: Discussioncontrasting
confidence: 65%
“…Most of the studies identified "cytokine storm" as the pathogenetic mechanism leading to fibrosis, based on the release of proinflammatory cytokines. In fact, aberrant inflammation associated with dysregulated repair mechanisms and fibrogenesis can lead to fibrogenesis (Bergantini et al, 2021b;Bergantini et al, 2022). Changes in the cellular and molecular environment in lung tissue secondary to viral infection, as found in COVID-19, were the key factors behind fibrosis development.…”
Section: Cytokine Pathways and Development Of Fibrosismentioning
confidence: 99%
“… 6 , 7 It is reported that changes in immune cells and different cytokines along with clinical and biochemical indexes can be served as predicting factors for clarifying disease severity and survival for patients with COVID-19. 8 The reduced numbers of lymphocytes and elevated levels of erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) are the most frequent abnormalities associated with COVID-19 and contribute to acute lung injury. 5 …”
Section: Introductionmentioning
confidence: 99%
“…Until now, many cytokines and chemokines along with immune cells have been investigated to clarify their roles in COVID-19 pathogenesis and provide a targeted personalized approach for its management. 8 , 9 Severe COVID-19 patients show the increased levels of IL-1, IL-8, IL-6, and tumor necrosis factor-alpha (TNF-α), and a decreased expression of IFN-γ. 6 , 10 , 11…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation